Cervicogenic Factor in Genesis of Trigeminal Vegetative Cephalalgias - YaroshevskiyO. А. (Psychiatry, Neurology and Medical Psychology, 2015)
The article is devoted to the modern ideas about trigeminal vegetative cephalalgias, and also the role of vertebro- muscular factor of neck comes into question in development of headache. The own clinical supervision of patient with SUNCT- a syndrome is presented. Positive dynamics of pain syndrome at aff ecting muscular disfunction of neck group of muscles for patients with trigeminal proves the necessity of vertebral-neurological research and treatment of disfunction of vegetative cephalalgias at as exposure for patients with the clinical displays of trigeminal vegetative cephalalgias.